The Rāmāyaṇa of Vālmīki: An Epic of Ancient India, Volume II : Ayodhyakāṇḍa - Vālmīki (Princeton Library of Asian translations., 2016)
This is the second volume of a translation of India's most beloved and influential epic saga, the monumental Rāmāyaṇa of Vālmīki. Of the seven sections of this great Sanskrit masterpiece, the Ayodhyakāṇḍa is the most human, and it remains one of the best introductions to the social and political values of traditional India. This readable translation is accompanied by commentary that elucidates the various problems of the text--philological, aesthetic, and cultural. The annotations make extensive use of the numerous commentaries on the Rāmāyaṇa composed in medieval India. The substantial introduction supplies a historical context for the poem and a critical reading that explores its literary and ideological components.